Success Strategies for Migrant Students: Optimizing Self-Regulated Learning and Academic Hardiness - Leonora Waworuntu, Gabriel; Astikasari Setya Murti, Heru (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Being a student away from home at Universitas Kristen Satya Wacana (UKSW) presents a significant challenge, as they often face various obstacles and demands throughout their academic journey. As students from outside the region, they must adapt to a new environment, which requires the development of self-regulated learning and academic hardiness. This study aims to explore the relationship between self-regulated learning and academic hardiness. The research uses a quantitative approach with a correlational design. A total of 140 students from UKSW Salatiga, Central Java, were selected as participants using purposive sampling, a method in which participants are chosen based on specific criteria relevant to the research objectives. The data were analyzed using Spearman’s Rho correlation test. The findings indicate a weak positive relationship between self-regulated learning and academic hardiness, with a correlation value of (r = 0.287 and sig. = 0.001). This suggests that an increase in self-regulated learning has the potential to enhance academic hardiness. The study is expected to provide insights showing that developing self-regulated learning can help UKSW students better face academic challenges. These findings offer valuable insights into the role of self-regulated learning in strengthening the academic resilience of students.Menjadi mahasiswa/i perantau di Universitas Kristen Satya Wacana (UKSW) merupakan tantangan yang tidak mudah, karena mereka sering menghadapi berbagai hambatan dan tuntutan dalam perjalanan akademik. Sebagai perantau, mahasiswa/i perlu menyesuaikan diri dengan lingkungan baru, yang mengharuskan mereka untuk mengembangkan self-regulated learning dan academic hardiness. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara self-regulated learning dengan academic hardiness. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Sebanyak 140 mahasiswa/i perantau dari UKSW Salatiga, Jawa Tengah, dipilih sebagai partisipan melalui teknik purposive sampling, yaitu pemilihan partisipan berdasarkan kriteria tertentu yang relevan dengan tujuan penelitian. Data dianalisis dengan menggunakan uji korelasi Spearman’s Rho. Hasil penelitian menunjukkan adanya hubungan positif yang lemah antara self-regulated learning dan academic hardiness, dengan nilai (r = 0,287 dan sig. = 0,001). Ini berarti bahwa peningkatan self-regulated learning berpotensi meningkatkan academic hardiness. Penelitian ini diharapkan dapat memberikan pemahaman bahwa dengan mengembangkan self-regulated learning, mahasiswa/i UKSW dapat lebih baik dalam menghadapi tantangan akademik. Temuan ini memberikan wawasan penting mengenai peran self-regulated learning dalam memperkuat kemampuan bertahan akademik mahasiswa-mahasiswi.